2017
DOI: 10.1136/acupmed-2016-011355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroacupuncture at Bl33 on Detrusor Smooth Muscle Activity in a Rat Model of Urinary Retention

Abstract: BackgroundDetrusor smooth muscle (DSM) underactivity may lead to urinary retention (UR). Electroacupuncture (EA) at BL33 may be effective in improving DSM contractions.ObjectivesThis study aimed to investigate: (1) the effect of EA at BL33; and (2) the effect of different manipulation methods at BL33 on the modulation of DSM contractions in UR rats.Methods30 male Sprague-Dawley rats were anaesthetised with urethane and modelled by urethral outlet obstruction. First, 2 Hz EA at BL33, SP6 and LI4 wasrandomly app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Relevant studies have found that acupuncture can activate the afferent nerve fibers of the dorsal root of the spinal cord [ 45 ]. Since the micturition center of BL33 and SP6 is located in the same segment, EA at these acupoints may activate sacral afferent nerve fibers to enhance bladder detrusor smooth muscle contraction [ 46 ]. Previous studies have reported that an increased bladder weight is correlated with increased bladder threshold capacity and residual urine [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Relevant studies have found that acupuncture can activate the afferent nerve fibers of the dorsal root of the spinal cord [ 45 ]. Since the micturition center of BL33 and SP6 is located in the same segment, EA at these acupoints may activate sacral afferent nerve fibers to enhance bladder detrusor smooth muscle contraction [ 46 ]. Previous studies have reported that an increased bladder weight is correlated with increased bladder threshold capacity and residual urine [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…SP6 is located 10 mm above the tip of the medial malleolus in rats. Since rats have only three pairs of posterior sacral foramina, we located the BL33 point at the second posterior sacral foramen [ 18 , 26 ]. Disposable sterile stainless steel acupuncture needles (0.25 mm × 25 mm; Cofoe Medical Technology Co., Ltd., Hunan, China) were inserted bilaterally at BL33 to a depth of approximately 15 mm and vertically inserted at SP6 to a depth of approximately 3 mm bilaterally.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electroacupuncture (EA) is an important method to prevent and treat DM and its complications ( Yao et al, 2021 ). BL23, BL33, and SP6 are acupoints widely studied in DM treatment (its common chronic complication) and bladder dysfunction ( Liu et al, 2017 ; Feng et al, 2018 ). BL28 corresponds to sacral vertebrae S2 and S3 levels; EA stimulation of the sacral vertebrae can inhibit an overactive bladder ( Feng et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%